ANALISIS PROSES PENGKLAIMAN PESERTA JHT BPJS KETENAGAKERJAAN KANTOR CABANG RANTAU PRAPAT - Ismu Hadi Siregar; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the claim process for Old Age Security (JHT) participants at the BPJS Employment Rantau Prapat Branch Office. The claims process is a crucial aspect of social security services, which directly influences participant satisfaction. The method used in this research is a qualitative-descriptive approach, with data collection through in-depth interviews and observations of claim participants and BPJS officers. The research results show that there are several factors that influence the smoothness of the claim process, including participants' understanding of the claim procedure, completeness of the documents submitted, and efficiency of service from officers. Apart from that, it was also found that participants often experienced obstacles, such as delays in processing claims and lack of clear information regarding claim status. This research recommends increasing socialization regarding claims procedures to participants and training for officers so they can provide better services. Thus, it is hoped that this analysis can make a positive contribution to improving the claims system at BPJS Employment, so that it can increase participant satisfaction and service effectiveness.